Jahrbuch der berufs- und wirtschaftspädagogischen Forschung 2016 - Seifried, Jürgen; Seeber, Susan; Ziegler, Birgit (Schriftenreihe der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2016)
What questions does vocational and business education research deal with? The current yearbook provides answers to these questions: it addresses questions about the organisation, conditions and structures of vocational education and training. It discusses approaches to the development of expertise, the structures of 'dual' or 'dualistic' vocational education and training and the consequences of the academicisation of vocational education and training. Further contributions focus on vocational teaching, learning and teaching research as well as questions of higher education and teacher training research, including the specificities of part-time degree programmes. Finally, the authors ask about the significance of continuing vocational training for companies and employees in the skilled trades and about approaches for assessing trainees in company practice. The yearbook concludes with an overview of historical vocational textbook research.